Periesophageal Pseudoaneurysms: Rare Cause of Refractory Bleeding Treated with Transarterial Embolization - Divyanshoo R. Kohli; Rachit D. Shah; Daniel J. Komorowski; George B. Smallfield (Case Reports in Gastrointestinal Medicine)
A 43-year-old female with history of systemic lupus erythematosus, prior cytomegalovirus esophagitis treated with ganciclovir, and long segment Barrett’s esophagus (Prague class C8 M9) with high grade dysplasia treated with radiofrequency ablation presented to the hospital with hematemesis. An upper gastrointestinal endoscopy showed multiple esophageal ulcers with active arterial spurting which could not be controlled with endoscopic interventions including placement of hemostatic clips. An emergent angiogram demonstrated actively bleeding saccular dilations (pseudoaneurysms) in the esophageal branches of the lower thoracic aorta as well as left gastric artery for which gelfoam and coil embolization was initially successful. Due to recurrence of massive bleeding, she subsequently underwent emergent esophagectomy and bipolar exclusion. Pathology demonstrated submucosal hemorrhage, esophagitis with dysplastic Barrett’s mucosa, and an ulcer containing cytomegaloviral inclusions. We report the first case of arterial bleeding from periesophageal pseudoaneurysms as well as use of angiographic embolization for arterial bleeding in the esophagus.